Conflict and Consensus : A study of values and attitudes in the Republic of Ireland and Northern Ireland - Hayes, Bernadette (European Values Studies, 2006)
This study presents a detailed comparison of cultural values and attitudes in the Republic of Ireland and Northern Ireland. It is based on survey data covering the period from the 1970s to 2003 but focusing especially on the European Values Study (EVS) as fielded in the two parts of Ireland in 1999-2000. The study confirms the deep divisions in identity and political allegiance that separate the Catholic and Protestant communities in Northern Ireland. But it also shows that on many issues, Protestants and Catholics on the island of Ireland are culturally more similar to each other than to any other national population in Europe, including Britain.